2023
DOI: 10.3389/fpsyg.2023.1067645
|View full text |Cite
|
Sign up to set email alerts
|

The spillover effect of work connectivity behaviors on employees' family: Based on the perspective of work-home resource model

Abstract: With the rapid development of mobile communication technology, work connectivity behaviors are becoming increasingly pervasive, which has gradually attracted extensive attention from scholars and practitioners. According to the work-home resource model, we propose a theoretical model that proactive/passive work connectivity behaviors induce family harmony through self-efficacy and ego depletion, and we explore the moderating role of family support in this relationship. Based on survey data collected from 364 q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Further studies have indicated that remote workers exhibited greater brain activity in regions associated with attention and focus, while office workers exhibited greater brain activity in regions associated with social cognition and interaction (Chen et al, 2023;Lee et al, 2023). For example, a study published in the journal Nature found that remote workers had significantly lower oxytocin levels in their cerebrospinal fluid, suggesting a reduced production of this neurotransmitter without regular face-to-face interaction (Kidd et al, 2013).…”
Section: Oxytocin Deficiency and The Stress Responsementioning
confidence: 99%
“…Further studies have indicated that remote workers exhibited greater brain activity in regions associated with attention and focus, while office workers exhibited greater brain activity in regions associated with social cognition and interaction (Chen et al, 2023;Lee et al, 2023). For example, a study published in the journal Nature found that remote workers had significantly lower oxytocin levels in their cerebrospinal fluid, suggesting a reduced production of this neurotransmitter without regular face-to-face interaction (Kidd et al, 2013).…”
Section: Oxytocin Deficiency and The Stress Responsementioning
confidence: 99%
“…Family support is a supportive resource provided by the family environment, including emotional understanding, practical help and information support ( Aryee et al, 2005 ; Michel et al, 2011 ), which can enhance employees’ vitality at work. The supportive resources from the family are mainly instrumental resources and emotional resources ( Aryee et al, 2005 ; He et al, 2023 ). For example, family members can help employees take the initiative to share household chores and take care of the elderly and children, which can objectively reduce the time pressure on employees in dealing with family matters, thus ensuring that they can have sufficient energy to devote to work and more time to develop their personal skills and knowledge and increase their work engagement.…”
Section: Theories and Hypothesismentioning
confidence: 99%